Predıctıon Of Mandıbular Growth Rotatıon In Retrognathıc And Orthognathıc Facıal Type - Erhan Özdiler; Dilek Erdem; Melike Uysal; Arzu Okul (Galenos Yayinevi, 1992)
This study was carried out on longitudinal profile radiographs obtained from 10 individuals with retrognathic facial type and 18 individuals with orthognathic facial type. The individuals of both groups mentioned above, are expected to have neutral mandibular growth rotation in future. Individual's facial type and expected direction of mandibular growth rotation was determined according to Hasund's criterion. Ricketts' short-range forecast method was used for prediction of mandibular growth rotation on the first profile radiographs which were taken during the initial stage of puberty (S stage). 1 index, 1 proportional, 11 angular and 3 linear measurements were performed not only on the tracings of prediction, but also on the tracings performed at the end of the study period. In each group, similarity between predicted values and observed values at the end of the study period (MP 3u stage) was evaluated statistically for each measurement.